2007
DOI: 10.1007/s11746-007-1184-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Frying Stability of Standard Palm Olein and Special Quality Palm Olein

Abstract: The main goal of this work was to investigate the stability of standard palm olein (SPOo) and special quality palm olein (SQPOo) under continuous frying conditions. The rate of free fatty acid (FFA) formation was slightly higher for SPOo than SQPOo during 56 h of frying. An equilibrium state was reached at around 40 h for SPOo and 32 h for SQPOo, whereby FFA varied within a narrow range of 0.30-0.32 and 0.22-0.25%, respectively. Smoke point of SPOo and SQPOo progressively dropped from 212 to 184°C and from 227… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 12 publications
2
38
1
4
Order By: Relevance
“…1 that the level of FFA was significantly lowered by more than two folds when frying is performed under continuous frying conditions. Similar trend is also obtained by Ahmad Tarmizi and Ismail 13,14 when produced potato chips under similar frying conditions. In this respect, it is plausible that the oil inside the fryer -which is taken up by the extruded product and/or loss during frying -is continuously compensated with the fresh oil of lower acidity and hence gives the consistency in FFA formation 14 .…”
Section: Free Fatty Acidsupporting
confidence: 85%
See 1 more Smart Citation
“…1 that the level of FFA was significantly lowered by more than two folds when frying is performed under continuous frying conditions. Similar trend is also obtained by Ahmad Tarmizi and Ismail 13,14 when produced potato chips under similar frying conditions. In this respect, it is plausible that the oil inside the fryer -which is taken up by the extruded product and/or loss during frying -is continuously compensated with the fresh oil of lower acidity and hence gives the consistency in FFA formation 14 .…”
Section: Free Fatty Acidsupporting
confidence: 85%
“…It is plausible that the frying temperature applied in this study was considerably low 155 in contrast to the conventional frying temperatures. Producing potato chips at 180 under continuous frying operation exhibited a decrease in the induction time during the first stage of frying before hovering within a constant value afterwards 13,14 . In fact, Ahmad Tarmizi and Ismail 14 even concluded that induction time has some relationship with the retention of vitamin E when palm olein is used for frying.…”
Section: Induction Timementioning
confidence: 99%
“…Studies by Matthaus (2007), Bracco et al (1981) and Faur (1975) indicated that PO and POo have similar frying performance compared with other high-stability oils. Tarmizi and Ismail (2008) demonstrated that frying stability of standard POo was comparable to special quality POo, and for use in the industrial production of snack foods. Standard POo is graded with maximum free fatty acids of 0.1% and peroxide value of 2-4 mequiv O 2 kg -1 .…”
Section: Frying/cooking Oilmentioning
confidence: 95%
“…The higher amounts of total polar compounds in palm oils are mainly due to a higher level of diacylglycerol contents (4.0-7.5%) compared to other vegetable oils (Berger, 2005;DeMarco et al, 2007). In the studies of fractions of palm olein, Plessis and Meredith (1999), Tarmizi and Ismail (2008) and Ismail (2005) determined polar compound values of 7%, 6.8-7.7% and 6%, respectively. In this study, the polar compound values of the samples produced in Bahia were more than double those reported in the literature.…”
Section: Changes In Oxidative Stabilitymentioning
confidence: 98%